25 years of child and adult psychiatric epidemiology studies in Puerto Rico - Canino, Glorisa (Puerto Rico Health Sciences Journal, 2007)
A review of the psychiatric epidemiology studies of the adult and child population of Puerto Rico carried out in the last 25 years is presented and discussed. Puerto Rico has experienced a plethora of psychiatric epidemiology studies since the decade of the 80’s, with 4 adult and 4 child population based studies. The overall results of these studies showed that island Puerto Ricans are not at greater risk for psychiatric disorders as compared to other US or international populations in spite of the fact that the island is besieged by many of the socio-demographic factors associated with high risk populations. If anything, it appears that important protective factors associated with good family relationships and the importance of the family in Hispanic families may be buffering island families from the development of addictive and antisocial disorders.